Complications Of Tads - Saify, Insiya; Shrivastava, Trilok; Shukla, Chandresh; Ali, Syed Akbar; Dixit, Siddharth; Patel, Aakash (Journal of Neonatal Surgery, 2025)
Temporary Anchorage Devices (TADs) have become an important adjunct in modern orthodontic treatment by providing reliable skeletal anchorage with minimal patient compliance. Despite their clinical advantages, various complications may occur during their placement and use. This article aims to review the common complications associated with TADs and their contributing factors. The most frequently reported complications include pain, soft-tissue irritation, inflammation, infection, screw loosening, and failure of primary stability. Root proximity, cortical bone perforation, and improper insertion techniques were also identified as significant risk factors. Patient-related factors such as oral hygiene and bone quality influence success rates. Operator experience and appropriate site selection play a crucial role in reducing complications. Early diagnosis and proper management strategies can improve treatment outcomes. Awareness of potential complications and adherence to correct clinical protocols can enhance the success and predictability of TAD-supported orthodontic treatment